Influence of liquefaction on scour behind coastal dikes due to tsunami overflow. Issue 1 (2nd January 2018) - Takegawa, Naoki; Sawada, Yutaka; Murai, Kazuki; Kawabata, Toshinori
Abstract : In the present study, hydraulic model experiments were conducted to clarify the influence of liquefaction on the scour behind coastal dikes due to tsunami overflow. In particular, the variation of the scour profile (scour depth, scour length and scour area) due to liquefaction was discussed. Degree of liquefaction was controlled by upward seepage, which was induced by the head difference between a water tank and a sand bed. Six hydraulic gradients were applied to the sand bed. The experimental results showed that liquefaction had a significant impact on the scour profile. At high hydraulic gradient, slope failures occurred due to reduction of effective stress of the sand bed. As a result, scour length was increased by the slope failures. Furthermore, the maximum scour depth and scour area for high hydraulic gradient became smaller than that for low hydraulic gradient.